Uptake of HIV Testing: Assessing the Impact of a Community-Based Intervention in Rural Nigeria - Onoja, Ali; Onoja, Sheila; Sanni, Felix; Adamu, Imam; Abiodun, Olaiya Paul; Shaibu, John (HEALTH SCIENCES AND DISEASE, 2020)
ABSTRACT Background. Voluntary counselling and testing (VCT) are the entry point for HIV/AIDS prevention and control for many community-based intervention programs. These VCT services are usually provided by Health care facilities. This study aims to assess the uptake of testing as a result of community-based intervention programs in a Nigerian rural community. Methodology. Quantitative survey that using a structured questionnaire among a sample of the general population aged 15 – 49 years. Demographic data (age, sex, education, occupation, marital status) and information related to HIV testing were sought. Data were analyzed using SPSS 25.0. Results. There were more male’s respondents (53.3%, baseline and 54.2%, post-intervention survey). The level of awareness of the availability of VCT services increased from 65.1% and 63.8% in males and females at the baseline survey to 89% and 87% in the post-intervention survey. The willingness to have HIV tests was relatively high in both surveys. overall, 16.1% have been tested in the baseline survey, this increased to 32.4% due to the intervention program. Before the interventions, the majority of the villagers were willing to do an HIV test because they only wanted to know their status and some just to reduce fear and anxiety. Intervention changes these perceptions as respondents in the intervention arm were willing to take up the test for marriage purposes and to know their status. Those that were unwilling to get testes were either not at risk or did not see any benefit in knowing their HIV status. The case was different after the intervention because the majority have been tested while there was a drastic decline in the number of those who think they were not at risk. Conclusion. This study found that the community-based health intervention in Bonny Island significantly contributed to the improved knowledge of VCT, willingness to get tested, and HIV testing uptake. More intervention programs towards the prevention of the spread of HIV in Nigeria is advocated. RÉSUMÉ Introduction. Le counselling et le test volontaires (CTV) sont le point d’entrée pour la prévention et le contrôle du VIH / SIDA dans de nombreux programmes d’intervention à base communautaire. Ces services sont généralement fournis par les établissements de santé. Le but de cette étude était d’évaluer l’utilisation des tests à la suite des programmes d’intervention à base communautaire dans une communauté rurale nigériane. Méthodologie. Il s’agissait d’une enquête quantitative qui a utilisé un questionnaire structuré auprès d’un échantillon de la population âgée de 15 à 49 ans. Nous avons recueilli des informations démographiques (âge, sexe, éducation, profession, état matrimonial) et des informations relatives au dépistage du VIH. Les données ont été analysées à l’aide de SPSS 25.0. Résultats. nous avons interrogé plus d’hommes (53,3%, base et 54,2%, enquête post-intervention) que de femmes. Le niveau de sensibilisation à la disponibilité des services de CTV est passé de 65,1% chez les hommes et 63,8% chez les femmes à 89% et 87% respectivement après l’intervention. La volonté de subir des tests de dépistage du VIH était relativement élevée dans les deux enquêtes. Dans l’ensemble 16,1% de sujets ont été testés avant intervention, et 32,4% après. Avant intervention, les motifs du dépistage étaient la connaissance du statut ou la réduction de la peur et l’anxiété. Après l’intervention les motifs étaient le désir de mariage et la connaissance du statut. Ceux qui refusaient le test n’étaient pas à risque ou ne voyaient aucun avantage à connaître leur statut VIH. Après l’intervention, la majorité d’entre eux ont été testés alors qu’il y avait une baisse du nombre de ceux qui pensaient qu’ils n’étaient pas à risque. Conclusion. L’intervention de santé communautaire à Bonny Island a contribué à l’amélioration des connaissances sur le CTV, la volonté de se faire tester et l’adoption du dépistage du VIH. Davantage de programmes d’intervention visant à prévenir la propagation du VIH au Nigéria sont préconisés.